Factors Influencing Infrastructure Risk Disclousure in Local Governments in Indonesia - Sabila Kartini; Henny Murtini (Journal of Accounting and Finance Management, 2026)
Infrastructure Risk Disclosure (IRD) is an important aspect of public sector transparency in local governments. This study examines the effect of Capital Expenditure (CE), Population (PT), Local Leaders’ Educational Background (LLEB), Regional Investment Income (RII), Regional Financial Independence (RFI), and Political Support (PS) on IRD using 235 observations and multiple linear regression with robust standard errors. The results show that only Population (PT) has a positive and significant effect on IRD, while other variables are not significant. Although the model is statistically significant, its low explanatory power suggests that other factors influence IRD. These findings indicate that population size, reflecting higher public demand and scrutiny, plays a key role in driving transparency, consistent with legitimacy theory. Future research should include governance and institutional variables to improve explanatory power.